RECLAMO: Unlocking the potential of wastewater reuse for agricultural irrigation in Spain - Irene Blanco-Gutiérrez (Pensoft Publishers, 2021)
Increasing water scarcity is encouraging the use of unconventional water resources. In recent years, the European Union has launched numerous initiatives to promote and facilitate water reuse for agricultural irrigation. Today, the use of reclaimed water for agriculture has become an alternative, reliable and safe source of water supply and an indispensable water planning tool, especially in the area of southern Europe. However, water reuse for irrigation is currently far below its potential. Numerous barriers prevent its development and call for a detailed analysis of the different aspects affecting reclaimed water reuse, through an integrated and multidisciplinary approach.A multidisciplinary research team from Universidad Politécnica de Madrid, consisting of agronomists, hydrologists, chemists and agricultural economists, will work on the RECLAMO Project (https://blogs.upm.es/reclamo/), with the aim of providing solutions and recommendations aimed at promoting the full development and use of reclaimed water for irrigation in areas of Spain with marked water stress.For this purpose, project activities will be developed in two selected case studies (the Segura Basin, leader in water reuse in Spain and the Guadiana Basin, with success stories, but low levels of water reuse) and organised according to five axes: 1) development of a comprehensive knowledge-base covering the regulatory, technical, socio-economic and environmental aspects of reclaimed water reuse in agriculture; 2) participatory development of future scenarios exploring possible strategies, barriers and opportunities, in relation to the expansion of the use of reclaimed water for irrigation; 3) impact analysis of  the strategies identified at different scales (crop, farm, (sub-)basin), through the development of an integrated modelling platform (hydrologic-agronomic-economic models); 4) Development of a roadmap and policy recommendations to achieve the full development and use of reclaimed water reuse for irrigation; 5) Dissemination of knowledge and promotion of science-policy-society dialogue.To this end, RECLAMO will collaborate closely with experts and stakeholder groups that will play a key role in the project in co-creating the scenarios and modelling tools and validating the results. The project will also seek for synergies and complementarities with other similar projects and explore new ways of collaborating with companies and research groups that allow research to continue and expand beyond the spatial and temporal limits of the project.RECLAMO’s results will promote an integrated approach to the sustainable management of water resources in water-stressed areas, including reclaimed water management. The integrated modelling platform developed in the project will allow policy-makers and water users to benefit from an improved understanding of the interactions between the social, economic and environmental aspects of water systems, in the context of climate and socio-economic change that will lead to better informed decision-making to address future water challenges. In addition, RECLAMO is expected to contribute to raising awareness about the use of reclaimed water reuse in agriculture as a safe and sustainable practice and to improve its social acceptance by producing science-based knowledge that provide evidence on the benefits derived from its use.